Fungal and Micotoxin contamination in mixed feeds: Evaluating risk in cattle intensive rearing operations (feedlots) - Gónzalez-Pereyra, M L; Chiacchiera, S M; Rosa, CAR; Dalcero, A M; Cavaglieri, L R (Revista Bio Ciencias, 2012)
Argentina is the fourth global beef producer. Exposure to mycotoxins through contaminated feed is a major hazard for ruminants. In the present study we assess mycobiota, aflatoxin B1 (AFB1), fumonisin B1 (FB1), deoxynivalenol (DON) and zearalenone(ZEA) levels in total mixed rations (TMRs) during two consecutive years. Total fungal counts were evaluated and fungal species were identified. Also, ability of A.flavus isolates to produce AFB1 in vitro wastested. Natural contamination with AFB1 and FB1 was quantified by HPLC. Deoxynivalenol and zearalenone were analysed by immunochromatography and thin-layer chromatography (TLC), respectively. Fungal counts varied from not detectable (ND) to 2.10 x 108 CFU g-1.The prevalent genera were Aspergillus spp(60 %) and Fusarium spp (66.7 %), respectively. The prevalent species was Aspergillusfumigatus. 50 % of A. flavus strains produced 75 to 112.5 μg g-1 AFB1. 46 % of 2007 sampleswere contaminated with 4 to 10 μg kg-1AFB1. Deoxynivalenol was detected in 33.3 % of the samples (≥ 1. 25 μg g-1). Fumonisin B1 and ZEA were not detected. This study can be usefulto estimate the mycotoxicological risk of cattle TMRs in this region and to compare results with studies from other beef-producing countries.